Public policies in headache disorders: needs and possibilities - PERES, Mario Fernando Prieto; OLIVEIRA, Arao Belitardo; SARMENTO, Elder Machado; ROCHA-FILHO, Pedro Sampaio; PEIXOTO, Patricia Machado; KOWACS, Fernando; GOULART, Alessandra Carvalho; BENSENOR, Isabela Judith (Arquivos de Neuro-Psiquiatria, 2020)
Although headaches have recognized impact, there are no public policies in Brazil addressing this problem. The Brazilian Headache Society and the Brazilian Association of Cluster Headache and Migraine promoted a summit to discuss Public Policy and Advocacy for headache disorders. Professionals from various segments, representing various sectors of society, gathered in April 2019 in Brasília, defining the most important points for achieving advances in public policies in headache in Brazil, such as: inclusion in the chronic diseases surveillance agenda; improving public understanding and access to diagnosis and treatment; teaching in colleges and medical residences, structuring care networks, intervention models, clinical protocols and legislation supporting public policies in headache.
Keywords: headaches; migraine; public policies